Efficiency of nalbuphine as an adjuvant to bupivancaine in lower limb orthopaedic surgery-a prospective study - Gupta, Kanhya Lal; Gupta, Amit; Neeraj, . (International Journal of Research in Medical Sciences, 2017)
Background: Spinal Anaesthesia is a well-known technique of performing lower limb orthopaedic surgeries. It has a shorter duration of action and early arising postoperative pain due to which various adjuvant needs to be added and their roles are being evaluated in various studies. Intrathecal opioids act synergistically with local anaesthetics and thus intensifying the sensory block without having any effect on sympathetic blockage. The main aim of present study is to investigate and evaluate the effectiveness of intrathecal nalbuphine (preservative free) as an adjuvant and also the efficacy of nalbuphine for postoperative analgesia and its complications if there are any. Methods: A total of 60 patients were included in this study belonging to ASA I and ASA II score with normal coagulation profile. Patients were randomly divided into 2 groups of 30 patients each. Group I receiving 3 ml of hyperbaric bupivacaine 0.5%+1.0mgm of nalbuphine (preservative free) injection made in 0.5 ml normal saline intrathecally. Group II received 3 ml of hyperbaric bupivacaine 0.5%+0.5 ml injection Normal saline intrathecally. The following criteria were noted. The onset of sensory blockade and complete motor blockade highest level of sensory blockade, duration of sensory blockade, duration of motor and duration of effective analgesia were recorded. Any hemodynamic alterations were also noted. Results: The mean time for the onset of sensory blockage was 56 sec in Group I and 59 sec in Group II (control). The difference were statistically insignificant (p>0.05). The mean onset of motor blockage was 106 sec in Group I and 208 sec in Group II (control). The difference was statically insignificant. The peak onset time in Group I and Group II was 372 sec and 220 sec respectively (p>0.05). Two segment regression times for sensory blockage was prolonged in Group I (118.20±8.56 min) compared to Group II (104.56±15.20 mins). Conclusions: The duration of postoperative analgesia was 6-8 hours in Group I compared to 3-4 hours in Group II (p value= 0.0001, statistically significant).